Charging, doping and gating of a single dangling bond on a bare Si(100)-c(4x2) surface - Mantega, Mauro (Trinity College (Dublin, Ireland). School of Physics, 2012)
Despite the increasing interest in novel materials for the next generation of microelectronic devices, such as graphene and topological insulators, Si(100) surface is still the most important substrate for nano-device applications. Its high stability and the possibility of manipulating and functionalizing the surface properties at an atomic level are opening up new perspectives for a wide range of applications ranging from transistor downscaling, dictated by Moore's law, to quantum computing.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.